Fish of Tuing-Tuing (Hydrundichthys Oxycephalus) as Abon Product - Miawati Mansur; Muhadjir Suni; Syahrial Manaf (Politeknik Pariwisata Makassar, 2024)
This study investigates the development of a new food product, specifically smoked tuing-tuing fish (Hirundichthys oxycephalus) abon, and assesses its acceptance among consumers. The objectives of the study purposes to find out the method for producing abon from smoked tuing-tuing fish meat, and to evaluate public preferences and acceptance regarding the final product’s characteristic, from the aspect texture, taste, aroma, and the colour of product. The research employs a quantitative methodology that combined with an experimental approach to create and refine the product. Data collection is comprehensive, involving primary sources such as direct observations and experiments, as well as secondary sources. Techniques used include detailed observations, experimental trials, structured questionnaires, and documentation throughout the experimental trial process to gather and analyze data. Eksperimental design as data analysis method is applied to interpret the results with data measurement using hedonic and sensory test. The result showed that smoked tuing-tuing fish can be effectively transformed into a desirable abon product. The final product of abon shows a distinctive brown color, noticeably smoked fish and spice aroma, a dry and non-greasy texture, and a flavorful of fish and savory taste. The hedonic and sensory tests indicate that the product meets high standards in all evaluated characteristics. Specifically, the product received positive feedback from respondent with high scores: 90% for texture, 93.2% for color, 92.6% for flavor, and 92.6% for taste. These scores place the smoked tuing-tuing fish abon in the “Very Like” category, reflecting strong consumer approval. So, it can be concluded that the research successfully demonstrates that smoked tuing-tuing fish can be utilized as a viable ingredient for producing fish abon. The high levels of acceptance and positive response from participants suggest that this product has significant potential in the market. The result underscore the viability of incorporating smoked tuing-tuing fish into new food products, highlighting the practical potential for this innovative approach. This research provides a solid foundation for further development and commercialization efforts, preparing for the introduction of a unique and marketable product.